Targeting Interleukin-2-Inducible T-Cell Kinase (ITK) Differentiates GVL and GVHD in Allo-HSCT - Mammadli, Mahinbanu; Huang, Weishan; Harris, Rebecca; Sultana, Aisha; Cheng, Ying; Tong, Wei; Pu, Jeffery; Gentile, Teresa; Dsouza, Shanti; Yang, Qi; Bah, Alaji; August, Avery; et al. (Frontiers in Immunology, 2020)
Abstract Allogeneic hematopoietic stem cell transplantation is a potentially curative procedure for many malignant diseases. Donor T cells prevent disease recurrence via graft-versus-leukemia (GVL) effect. Donor T cells also contribute to graft-versus-host disease (GVHD), a debilitating and potentially fatal complication. Novel treatment strategies are needed which allow preservation of GVL effects without causing GVHD. Using murine models we show that targeting IL-2-inducible T cell kinase (ITK) in donor T cells reduces GVHD while preserving GVL effects. Both CD8+ and CD4+ donor T cells from Itk-/- mice produce less inflammatory cytokines and show decrease migration to GVHD target organs such as the liver and small intestine, while maintaining GVL efficacy against primary B-cell acute lymphoblastic leukemia (B-ALL). Itk-/- T cells exhibit reduced expression of IRF4 and decreased JAK/STAT signaling activity, but upregulating expression of Eomesodermin (Eomes) and preserve cytotoxicity, necessary for GVL effect. Transcriptome analysis indicates that ITK signaling controls chemokine receptor expression during alloactivation, which in turn affects the ability of donor T cells to migrate to GVHD target organs. Our data suggest that inhibiting ITK could be a therapeutic strategy to reduce GVHD while preserving the beneficial GVL effects following allo-HSCT treatment.